#### Question

Evaluate the following using identities:

(2x + y) (2x − y)

#### Solution

In the given problem, we have to evaluate expressions by using identities.

We have been given (2x + y) (2x − y)

We shall use the identity `(a + b)(a - b)= a^2 -b^2`

Here a = 2x, b = y

By applying identity we get

`(2x + y)(2x - y) = (2x)^2 - (y)^2`

`= (2x xx 2x) - (y xx y)`

`= 4x^2 - y^2`

Hence the value of (2x + y)(2x - y) is `4x^2 - y^2`

Is there an error in this question or solution?

Solution Evaluate the Following Using Identities: (2x + Y) (2x − Y) Concept: Algebraic Identities.